EDUCATION EFFECT OF ACUTE HEPATITIS IN UNKNOWN CAUSES ON KNOWLEDGE OF HEALTH WORKERS AND STUDENTS - Ikbal Fradianto; Arief Andriyanto; Kharisma Aji Martadi; Nita Arisanti Yulanda (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Acute hepatitis is one of the world's health problems, especially in children whose exact cause is unknown. Cases of acute hepatitis continue to increase, but due to unknown causes, the introduction and treatment of this case are relatively new in the community and among health workers. The purpose of this study was to determine whether education affects acute hepatitis in children whose cause is unknown to the knowledge of health workers and students. The sample in this study amounted to 167, consisting of health workers and students. The results showed a change in the mean before being given acute hepatitis education to children whose cause was unknown and after. There is an effect of acute hepatitis education in children whose cause is not known to the knowledge of health workers and students.